Measures of patient safety in developing and emerging countries: a review of the literature. Issue 1 (19th February 2010) - Carpenter, K B; Duevel, M A; Lee, P W; Wu, A W; Bates, D W; Runciman, W B; Baker, G R; Larizgoitia, I; Weeks, W B
Abstract : Context: The World Alliance for Patient Safety was formed to accelerate worldwide research progress towards measurably improving patient safety. Although rates of adverse events have been studied in industrialised countries, little is known about the rates of adverse events in developing and emerging countries. Purpose: To review the literature on patient safety issues in developing and emerging countries, to identify patient safety measures presently used in these countries and to propose a method of measurably improving patient safety measurement in these countries. Methods: Using the Medline database for 1998 to 2007, we identified and reviewed 23 English-language articles that examined patient safety measurement in developing and emerging countries. Results: Our review included 12 studies that prospectively measured patient safety and 11 studies that retrospectively measured safety. Two studies used measures of structure and the remaining used process measures, outcome measures or both. Whereas a few studies used surveys or direct observation, most studies used chart audits to measure patient safety. Most studies addressed safety at a single facility. Conclusions: Investigation of patient safety in developing and emerging countries has been infrequent and limited in scope. Establishing fundamental safe patient practices, integrating those processes into routine health services delivery and developing patients' expectations that such processes be present are necessary prerequisites to measuring and monitoring progress towards safe patient care in emerging and developing countries.